Plantas ornamentales en conucos de tres regiones de Cuba - Fuentes Fiallo, V.R.=700 1 Suarez, R.C.; Shagarodsky Scull, T.; Sanchez Perez, P.; Castiñeiras Alfonso, L.; Fundora Mayor, Z.
(En, Fr, Es)
ilus., 14 ref.
Keywords: PLANTAS ORNAMENTALES; CONSERVACION DEL GERMOPLASMA; CUBA